Flamenco Negro:: analysis of the spectacle by Companhia De Arte La Negra Ana Medeiros - Andreoli, Giuliano (Revista Brasileira de Estudos da Presença, 2023)
This paper proposes an analysis of the spectacle Flamenco Negro, based on the theoretical framework of the sociology of art and the sociology of ethnic-racial relations, combining the analysis of the social context of production of the work with the methodology of performance analysis. The study found that the process of creating such a work of art was part of a social network articulating a community of meaning that helped to form the dancers’ own racial consciousness, enabling them to reaffirm their position and their way of dancing within the art scene and resize the black diaspora as a collective experience by highlighting the hybridity between Afro-diasporic dances and musicalities in Flamenco.